A legal analysis of the Malaysian anti-corruption commision’s independence under the legislative framework of the Malaysian Anti-Corruption Commision Act 2009 / Afzan Mohammad Azahar … [et al.] - Mohammad Azahar, Afzan; Abdul Nasir, Nuraqilah; Mat Zaki, Nurul Thahirah; Mat Yusoff, Shukriah (2009)
For this semester we have been conducting a research on the legal analysis of the Malaysian Anti-Corruption Commission s (MACC) independence under the legislative framework of the Malaysian Anti-Corruption Commission Act 2009. Instead of looking to the law, we also look and compared with the Hong Kong and Australian on the issue of corruption. We also found there are loopholes in the Act in order to uphold the independent of the MACC. In completing our research, we had conducted a traditional research which is library based this is due to the absentness of the sources since this Act come into force in 2009.After a 3months period we finally finished doing our project on the a study of independence of MACC.